The Interesting Narrative of the Life of Olaudah Equiano - Equiano, Olaudah (Saga Egmont, 2022)
Sometimes true life spins more shocking stories than the minds of writers. That is the case with \'The Interesting Narrative of the Life of Olaudah Equiano\'. The understated title masks an autobiography where truth trumps fiction, featuring kidnapping, death, slavery, jail, transportation, rape, Christian faith and much more.It is also one of the most important books of its time, the late 18th century. For its publication told the truth about the trans-Atlantic slave trade, and sowed the seeds for the abolition movement that eventually stopped it.The scandal of slavery that Equiano helped get into the public\'s consciousness has been featured in a host of films, including \'12 Years a Slave\', directed by Steve McQueen and based on a novel by Solomon Northup.